FOLLOWING TO THE LETTER: THE LITERAL USE OF SCRIPTURE - Loughlin, Gerard (1995)
This essay for an understanding of the literal sense of Scripture after its diremption in the modern period between the written and the historical. It introduces John Spong as exemplary of a liberal tendency to disparage the literal, and Hans Frei as showing how the sensus literals was, and may be again, found in the ‘world’ of the scriptual narrative, and how it came to be dirempted Finally I argue that the literal sense of Scripture is locatable in the mutual constitution of Church and Scripture, of text and reading-community The literal and historical are rebound insofar as the Church performs the letter of the text.